The Legal Basis of Electronic Signatures in Civil Dispute Evidence in Indonesia: A Study of the Indonesian Information and Electronic Transactions Law (ITE Law): Dasar Hukum Tanda Tangan Elektronik dalam Pembuktian Sengketa Perdata di Indonesia: Kajian Terhadap Undang-Undang Informasi dan Transaksi Elektronik Indonesia (UU ITE) - Arbaya, Nisma Raditya; Baidhowi, Baidhowi (Faculty of Law, Universitas Negeri Semarang, 2024)
Documents signed electronically using electronic signatures are governed by the Indonesian Information and Electronic Transactions Law (ITE Law), which regulates electronic information, electronic documents, and/or their printed results. According to the ITE Law, printed results, electronic documents, and/or electronic information are all considered valid additional evidence that can be used in court. These pieces of evidence constitute an extension and valid evidence according to the applicable procedural law in Indonesia and are also valid evidence in court. The research technique used to compile this article is literature research or normative juridical method, classified as legal research. Several court decisions have defined the legal authority of electronic signatures from the perspective of civil law. Thus, it is clear that from the perspective of civil law, electronic signatures have the same legal force as traditional signatures made with wet ink and have legal consequences. The considerations of judges in civil judgments consist of two parts: factual considerations, which are the evidence submitted by the parties, which party's evidence reaches the minimum threshold of proof, what arguments are proven, and to what extent the probative value held by the parties. The second part relates to legal considerations, including articles in statutory regulations and unwritten law as the basis for making judgments.